How the West Came to Rule The Geopolitical Origins of Capitalism - Anievas, Alexander (Pluto Press, 2015)
Mainstream historical accounts of the development of capitalism describe a process which is fundamentally European - a system that was born in the mills and factories of England or under the guillotines of the French Revolution. In this groundbreaking book, a very different story is told. The book offers a unique interdisciplinary and international historical account of the origins of capitalism. It argues that contrary to the dominant wisdom, capitalism's origins should not be understood as a development confined to the geographically and culturally sealed borders of Europe, but the outcome of a wider array of global processes in which non-European societies played a decisive role. Through an outline of the uneven histories of Mongolian expansion, New World discoveries, Ottoman-Habsburg rivalry, the development of the Asian colonies and bourgeois revolutions, the authors provide an account of how these diverse events and processes came together to produce capitalism.